The Campaign in Mesopotamia 1914-1918 : History of the Great War Based on Official Documents (Vol.3) - Moberly, F. J. Gen. (London Majesty's Stationary Office, 1925)
This third volume in the official four-volume history of the Mesopotamia (Iraq) campaign takes the story form May 1916 up to 30 April 1917, covering the battle of Kut-Al-Amara, the pursuit of the Turks, the occupation of Baghdad and the subsequent opérations around Baghdad... Operations here are described in detail, since this phase in the Mesopotamian campaign is the only instance of continuous, close-trench fighting. Appendices provide detailed British and Indian army order of battle information.
Include Illustration and Index
Keywords: World War (1914-1918) -- Iraq -- Military campaigns